Adolescent manifestations of metabolic syndrome among children born to women with gestational diabetes in a general-population birth cohort. - Vääräsmäki, M; Pouta, A; Elliot, P; Tapanainen, P; Sovio, U; Ruokonen, A; Hartikainen, A; Mccarthy, M; Järvelin, MR (2009)
The association between maternal gestational diabetes (GDM) and manifestations of metabolic syndrome among Caucasian adolescents was studied with data from the population-based Northern Finland 1986 Birth Cohort. This is a longitudinal cohort study from early pregnancy until offspring age 16 years and includes data from a risk group-based GDM screen of pregnant mothers by an oral glucose tolerance test. Metabolic outcomes were compared between the offspring of women with GDM (OGDM; n = 95) and reference group offspring (n = 3,909). The prevalence of overweight was significantly higher in the OGDM group (18.8 vs. 8.4%; P < 0.001) than in the reference group. The median body mass index (20.8 vs. 20.2 kg/m(2), 95% confidence interval (CI) for the percentage difference adjusted for sex: 3.5%, 9.5%), waist circumference (73.3 vs. 71.5 cm, 95% CI: 3.2%, 7.5%), and fasting insulin (10.20 vs. 9.30 milliunits/L, 95% CI: 5.9%, 26.0%) were higher, and homeostatic model assessment-insulin sensitivity (74.7 vs. 82.3, 95% CI: -20.6%, -5.4%) was lower in the OGDM group. These differences were similar after an additional adjustment for birth weight and gestational age. The differences in waist circumference, insulin, and homeostatic model assessment-insulin sensitivity were attenuated but remained statistically significant after additional adjustment for body mass index at 16 years. These findings highlight the importance of prevention strategies among children born to women with GDM.